Radiological assessment of wastewater treatment processes based on the use of coal ashes as a filters - Taoufiq, L.; Laamyem, A.; Boukhair, A.; Essediqi, E.; Monkade, M.; Zrabda, A. (Journal of Radiation Research and Applied Sciences, 2018)
Coal Fly Ash and Coal Bottom Ash are a solid waste generated from coal combustion. Recently, the management of these wastes has become an important subject for environmental researchers. Due to their physical and chemical characteristics, coal ashes were used in different fields like building material, agriculture and wastewater treatment. In the present investigation, a radiological assessment of Waste Water Treatment Plant (WWTP) based on the use of coal ashes as filters was performed. The WWTP under investigation uses four stages of treatment: Coal Fly Ash filtration, Coal Bottom Ash filtration and sand filtration. Radiation risk of coal ashes was evaluated by 2 techniques: Dosimetry alpha based on the use of LR115 detector and gamma ray spectrometer. The surface exhalation rate in coal ash samples were found to be below the world average 57600 mBq∙m−2 h−1 and most of the coal ash samples show the value of Raeq less than the allowed upper limit of 370 Bq kg−1. Moreover, the radon concentration of water samples during the treatment were evaluated for each stage in order to identify if there was any impact of coal ashes on the treated water. Radon activity of treated water remains in the standards with a average value of 196 ± 13 (Bq/m3) less far than the permissible limit (11100 Bq/m3). The obtained results indicate that the radiological characteristics of the treated water was not influenced by radiological characteristics of coal ashes. It be concluded that coal ashes from TAQA Morocco are a safe materials and did not present a significant radiological risk which make them a suitable material for wastewater treatment. •New conception of WWTP based on the use of coal ashes as a filters.•A radiological assessment in coal ashes were conducted before use it.•Coal ashes are a safe material and can be used as filters in wastewater treatment.•Radon concentration in water was monitored at each stages of treatment.•The outgoing water radioactivity remains the standards.